Transcriptome Analysis Reveals Norathyriol Prolongs the Lifespan via Regulating Metabolism in C. elegans - Hong-Jia Zhang; Hai-Quan Lan; Meng-Ying Wang; Cai-Feng Wang; Lu-Gang Wei; Chen Xu (Metabolites)
Background: Aging and age-related diseases are closely linked to an imbalance in energy supply and demand, a condition that can potentially be mitigated through various interventions, including the use of naturally occurring molecules. Norathyriol (NL), a tetrahydroxyxanthone compound, is prevalent in mango fruit and medicinal plants. While studies have indicated that NL may influence metabolism, its effects on aging have not been extensively explored. Methods: We conducted lifespan analysis and measured lipofuscin accumulation in C. elegans model to evaluate the effects of NL on aging. Additionally, we identified differentially expressed genes (DEGs) through comprehensive RNA-sequencing (RNA-seq) analysis and performed gene ontology (GO) and kyoto encyclopedia of genes and genomes (KEGGs) pathway analyses to elucidate the molecular mechanisms underlying NL’s effects. Results: Our study demonstrated that NL at 50 μM extends the lifespan by 15.9% and reduces lipofuscin accumulation in C. elegans without impacting their feeding capabilities. A total of 928 DEGs were identified in NL-treated worms. The analysis of DEGs indicated that NL’s longevity-promoting effects might be due to its regulation of gene expression in lipid metabolism and immune response pathways. Furthermore, the insulin/insulin-like growth factor (IGF)-1 and target of rapamycin (TOR) signaling pathways were implicated in the lifespan-extending effect of NL. Conclusions: These findings broaden the bioactivity profile of polyphenols and highlight the need for further investigation into the therapeutic potential of NL in combating age-related diseases.